Geochemical composition of fluvial sediments in the Milo River basin (Guinea): is there any impact of artisanal mining and of a big African city, Kankan?. (September 2018) - Sow, M.A.; Payre-Suc, V.; Julien, F.; Camara, M.; Baque, D.; Probst, A.; Sidibe, K.; Probst, J.L.
Abstract: For the first time, the bed sediments of the Milo River and its tributaries were sampled and analyzed to characterize their geochemical signature in terms of major, trace and rare earth elements and to determine the potential impacts of artisanal mining and of the anthropogenic activities of Kankan city. 24 sites have been sampled along the Milo river from upstream to downstream and on its tributaries during one sampling campaign to assess the spatial variations of the geochemical signature. During one year, the bed sediments have been sampled monthly on the Milo river upstream and downstream Kankan to determine the seasonal variations of their chemical composition and to investigate the potential impacts of Kankan on the fluvial sediment quality. The geochemical signatures of the sediments are mainly controlled by the geological substratum and the lateritic soil cover, showing that there is no impact of the artisanal mining and very few impacts of Kankan, except for As and Sb on two small tributaries draining the urban agglomeration. All the sediments are more concentrated and naturally enriched in Zr, Hf, U and Th compared to PAAS, due to the regional geochemical background. REE distribution patterns show LREE and HREE enrichments and positive Ce and Eu anomalies. The La/Yb ratios are positively correlated to Al and Fe-oxides and negatively to silica. The non-residual fractions (labile) extracted with EDTA represent less than 20% of the total concentration, showing that the threats for aquatic ecosystems and human populations are limited. This study can represent a reference with regard to the potential development of industrial mining and increase of population due the abundant mineral resources within this catchment. Graphical abstract: Image 1 Highlights: First data on major, trace and rare earth elements for Milo river bed sediments. Zr, Hf, U and Th enrichments controlled by geological substratum and lateritic soils. No evidence of the artisanal mining impact on trace element and REE concentrations. Few impacts of Kankan city activities on the Milo bed sediments, except As and Sb. Low % of labile trace elements in bed sediments : no threat for aquatic ecosystems.